FACTORS AFFECTING BEHAVIORAL INTENTION TO USE MOBILE BANKING SERVICES - Amelia, Mona; Ronald, Jimi; Syamra, Yesmira; Pratama, Indra Mulia; Putri, Yosi Eka (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2024)
Our research aims to reveal factors that are considered effective in influencing intentions to use mobile banking services, especially those owned and managed by Bank Nagari Padang Main Branch. In our research, the population used was all customers who saved at Bank Nagari Main Branch in Padang, while the samples were 100 customers who had saved through Bank Nagari Main Branch for more than a year and were over 17 years old. The data collection stage was carried out by a survey, namely by distributing questionnaires directly to target respondents who met predetermined criteria. The analytical method used is multiple linear regression (OLS) and t-statistical testing. In accordance with the results of hypothesis testing, we found that three dimensions of the Unified Theory of Acceptance and Use of Technology (UTAUT), namely performance expectancy, effort expectancy and social influence, have a positive and significant effect on the intention to use Bank Nagari's mobile banking services, while the other dimension is Facilitating conditions do not have a significant influence on customers' intentions to use Bank Nagari's mobile banking services. Thus, it can be concluded that the hope of obtaining maximum benefits, the ease of operating procedures for technology-based devices, as well as the large influence of the social environment have an important role in shaping the intentions of Bank Nagari Padang Main Branch customers to use mobile banking services.